Translations of the meanings of Surah Al-Rahman into Hebrew A critical linguistic study (Journal of the College of Basic Education, 2022)
Active translation of the Holy Quran into Hebrew during the twentieth century in order to search or just for general knowledge and culture. It was not intended to target religious. The Jews know who lived in the Middle Ages on the Quran from its primary source linguistically by virtue of their knowledge of the Arabic language. These translations came between partial translations of some of its verses or AL. Anyone who approached the translation of the Holy Quran from the Jews was acting in translation according to his vision and his personal knowledge Arabic. therefore differed in the level of precision in understanding the meanings in the text of the Quran. This is called projection. It was noted that the impulse to drop is the feeling of inferiority and the inferiority based. That the purpose of the process is to defend the projection defects or deficiency in the existing. And make a projection is subconsciously. And that the target you are signing projection it - often – have what guides him through the process of projection. It highlighted what he did to some translators Jews is dropping concepts on the concept of Jewish religious (God) in the Quran, or drop the concepts of Judaism during the translation, or the treatment of the Quran as no different from the rest of the humanitarian action. Sura Rahman more Quranic fence that need has been achieved a good understanding of the text